Oro-Facial manifestations of COVID-19 infection in a sample of Iraqi people - Noor H. Mohammad; Ahmed Y. Hameed; Aysar N. Mahmood (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Public health officials are gravely concerned about the harm that viral illnesses continue to pose to humanity, various viral outbreaks, including the Middle East Respiratory Syndrome Corona-Virus (MERS-CoV), H1N1 influenza, the severe acute respiratory syndrome coronavirus (SARS-CoV-2) and SARS CoV-2 or COVID-19 that struck the globe in December 2019. A wide range of COVID-19 oral symptoms, such as ulceration, blisters, enanthems, hemorrhagic sores and cheilitis. Aim: to investigate the prevalence of oral symptoms amongst COVID-19 patients due to the disease's aggressive nature and diverse symptomatology and to assess the impact of oral health conditions on COVID19 disease severity in a sample of Iraqi people. Materials & Methods: a cross-sectional study was conducted on (200) patients in total, (81) male and (119) female, who were identified as SARS-COV2 patients. Results: COVID confirmed patients were involved in the present study with mean age (36.69±17.22) years & age range of (16-78) years. at least one of the oral manifestations was present in 72.5% of the patients, while about 27.5% did not experience any oro-facial symptoms. The oral symptom with the highest prevalence was dry mouth 50% followed by gustatory dysfunction 37% then burning mouth sensation 22.5% after that the oral pain 17%; myofacial pain 15.5 %; stomatitis\mucositis 14.5%; the prevalence of aphthous lesions, fissural cheilitis and tongue depapillation were at the same percentage which was 9.5%; then candidiasis 7.5%; the least prevalent oral symptoms was gingival bleeding at percentage of 2.5%.Conclusions: COVID-19 has a noticeable effect on oral cavity, there was a correlations between some general and orofacial manifestations of COVID-19.